2018
DOI: 10.1097/md.0000000000010133
|View full text |Cite
|
Sign up to set email alerts
|

Higher stroke incidence in the patients with pancreatic cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
(32 reference statements)
1
18
0
Order By: Relevance
“…In addition, we also analyzed the time sequences between the initiation of chemotherapy, development of aTE, and patient’s death. Several studies reported the peak incidence of ischemic stroke happened within first 6 months of cancer diagnosis [ 11 , 24 ] and the medial survival after ischemic stroke was around 1 to 4.5 months [ 15 , 16 ]. The peak incidence of aTE and survival outcome after the diagnosis of aTE was comparable with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also analyzed the time sequences between the initiation of chemotherapy, development of aTE, and patient’s death. Several studies reported the peak incidence of ischemic stroke happened within first 6 months of cancer diagnosis [ 11 , 24 ] and the medial survival after ischemic stroke was around 1 to 4.5 months [ 15 , 16 ]. The peak incidence of aTE and survival outcome after the diagnosis of aTE was comparable with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies are beginning to explore the association between pancreatic cancer and aTE [ 10 , 23 , 24 ]. However, due to the rarity of aTE and the inherent limitations imposed by the national registry data [ 24 ], data regarding the risk factors and the impact of aTE on survival outcome in patients with pancreatic cancer were limited. Palliative chemotherapy is the standard treatment for patients with unresectable or metastatic pancreatic cancer and unfortunately, the impact of chemotherapy on the overall incidence of aTE has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the annual age-standardized incidence rate of diabetes was <1% across Taiwanese population (Jiang et al, 2012). Additionally, the age and gender-adjusted incidence of AMI was 50.7/100,000 persons in 2015 (Lee et al, 2018) and the estimated stroke incidence was 12.3/1000 person-years (Chan et al, 2018). Our results highlight the need for studies to determine the impact of TB disease on risk of NCDs; such studies will require substantial follow-up time and a control group without TB disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells can activate the body's coagulation mechanism by releasing many tissue factors, cancer-associated procoagulant, and cyokines, and cancer cells also can interact with platelets to release ADP, arachidonic acid, 5-HT, and other substances to promote blood coagulation. Eventually, the body will be hypercoagulable [23][24][25][26][27]. Bang's recent research showed circulating tumor extracellular vesicles, especially in adenocarcinoma patients, also played a vital role in cancer-associated thrombosis and tumor progression [28,29].…”
Section: Discussionmentioning
confidence: 99%